Efficacy of intralesional injections of platelet‐rich plasma in patients with oral lichen planus: A pilot randomized clinical trial - AbdelHameed Hijazi; Wesam Ahmed; Soheir Gaafar (Wiley, 2022)
Abstract Objective To evaluate the clinical efficacy of intralesional platelet‐rich plasma (PRP) injections compared to intralesional triamcinolone acetonide (TA) injections in the treatment of erosive oral lichen planus (EOLP). Material and Methods Twenty patients with EOLP were assigned randomly to either PRP or TA group. Patients received weekly intralesional injections for 4 weeks, and then followed up for 3 months on regular visits every 2 weeks. Pain scores using numerical pain score and clinical score were recorded by a blinded assessor each visit for all patients and remission score at the end of the trial was recorded. Results Both groups showed significant improvement in the clinical parameters (pain and clinical score) "p = .001." Regarding remission of the lesions, 80% of patients in the PRP group showed complete remission compared to 70% in the TA group. However, there is no statistical significance when comparing the two groups in pain score, clinical score, or remission. Conclusions PRP injections could be considered as an effective alternative single treatment modality for EOLP. The protocol for this study registered in Clinicaltrials.gov registry under the identifier number: NCT03293368.